KEPUASAN WISATAWAN TERHADAP PENERAPAN PROTOKOL KESEHATAN CLEANLINESS, HEALTH, SAFETY, & ENVIRONMENTAL SUSTAINABLE (CHSE) DI LABUAN BAJO NUSA TENGGARA TIMUR - Tandilino, Sari Bandaso (Jurusan Pariwisata Politeknik Negeri Kupang, 2024)
The tourism industry has been one of the sectors most affected by the Covid-19 pandemic, as it was impacted the earliest, faced the highest risk of losses, and is experiencing the slowest recovery. By 2020, only 13% of the tourism industry in Indonesia had achieved CHSE certification, compared to the government’s target of 44,670. This situation has caused many tourists to be hesitant and unwilling to visit tourist destinations in NTT, particularly Labuan Bajo on Flores Island. It has put millions of livelihoods at risk and threatens the progress made towards the Sustainable Development Goals (SDGs). The aim of this research is to assess international tourists' satisfaction with the implementation of CHSE protocols in Labuan Bajo. Data collection will be conducted through distributing questionnaires and analyzing them using both quantitative and qualitative data analysis techniques. The study's results show that the satisfaction score for the alignment of importance and expectations in Labuan Bajo, Flores, is 94%, which falls into the